God, the Good, and Utilitarianism : Perspectives on Peter Singer / [electronic resource] - Perry, John (Cambridge : Cambridge University Press, 2014)
Is ethics about happiness? Aristotle thought so and for centuries Christians agreed, until utilitarianism raised worries about where this would lead. In this volume, Peter Singer, leading utilitarian philosopher and controversial defender of infanticide and euthanasia, addresses this question in conversation with Christian ethicists and secular utilitarians. Their engagement reveals surprising points of agreement and difference on questions of moral theory, the history of ethics, and current issues such as climate change, abortion, poverty and animal rights. The volume explores the advantages and pitfalls of basing morality on happiness; if ethics is teleological, is its proper aim the subjective satisfaction of preferences? Or is human flourishing found in objective goods: friendship, intellectual curiosity, meaningful labour? This volume provides a timely review of how utilitarians and Christians conceive of the good, and will be of great interest to those studying religious ethics, philosophy of religion and applied ethics.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Utilitarianism; Good and evil; Christian ethics